QGIS Simulation Using Openstreetmap Data on Pedestrian Routes from Schools to Green Open Spaces - Nuzir, Fritz Akhmad; Rizki, Muhammad Fathur; Maulana, Daus (International Journal of Building, Urban, Interior and Landscape Technology, 2025)
Green open spaces play an important role in modern urban development, benefiting both the ecology and the quality of life of city dwellers. Functional pedestrian path is an important element to support the accessibility of green open spaces. Commonly in Indonesia, green open spaces are isolated and disconnected from pedestrian path network. This research used spatial analysis combined with descriptive method to elaborate systematically and factually, regarding the accessibility of the fastest and shortest routes of pedestrian paths from selected schools to Lampung Elephant Park in Bandar Lampung, as the observed green open spaces. Authors suggested that the connection between schools and green open spaces is important in relation to facilitated environmental and physical education. Field observations and software simulation using QGIS based on OpenStreetMap were utilized to analyse the existing pedestrian path and to indicate the shortest routes. The simulation could suggest routes that accommodate comfortable walking times. The findings from this research can serve as valuable recommendations for urban planning, specifically aimed at enhancing pedestrian accessibility to green open spaces. Priority could be given to improving walking infrastructure along the proposed pedestrian pathways by closely addressing any unmet requirements. Future studies will explore advanced simulation techniques to further refine and optimize these recommendations.